1991
DOI: 10.1002/bjs.1800780915
|View full text |Cite
|
Sign up to set email alerts
|

Graft versus host disease in small bowel transplantation

Abstract: Quantities of organized lymphoid tissue in small bowel allografts may cause graft versus host disease (GVHD) following transplantation. This study examines the effect of graft mesenteric lymphadenectomy on development of GVHD following small bowel transplantation in rats. GVH reactivity was assessed by measuring the degree of graft cell emigration to the host. In the PVG to DA strain combination, graft mesenteric lymphadenectomy led to a significant reduction in graft cell colonization of host lymphoid tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…This result is consistent with a previous report that graft mesenteric lymphadenectomy prevented GVHR only in certain strain combinations. 9 The present results suggest that the intestinal mucosal layer has an important immunological role in small-bowel transplantation-induced GVHR. Indeed, it has already been reported that small-bowel-transplantation-induced GVHR depends on the length and site of origin.…”
Section: Small-bowel Transplantationsupporting
confidence: 51%
“…This result is consistent with a previous report that graft mesenteric lymphadenectomy prevented GVHR only in certain strain combinations. 9 The present results suggest that the intestinal mucosal layer has an important immunological role in small-bowel transplantation-induced GVHR. Indeed, it has already been reported that small-bowel-transplantation-induced GVHR depends on the length and site of origin.…”
Section: Small-bowel Transplantationsupporting
confidence: 51%
“…The time to development of chronic rejection is variable and has ranged from as little as 2 months to years posttransplant. recipient s peripheral blood and bone marrow (Clark et al 1991 ;Morrissey et al 1999 ;Shin et al 2011 ;Andres et al 2010 ). Clinically, it is characterized by persistent diarrhea with bleeding and increased stomal output.…”
Section: Hsv and Vzv Infectionmentioning
confidence: 99%
“…GVHD after intestinal transplantation is reported to be caused by the large number of cytotoxic T cells (CTLs) contained in the graft gut-associated lymphoid tissue (GALT) [1]. GALT, including intraepithelial T lymphocytes (IELs), is a phenotypically unique population among peripheral T cells, consisting of a large percentage of ␥␦ T cells [2], which have recently been reported to induce GVHD in such target organs as the liver [3].…”
Section: Introductionmentioning
confidence: 99%